The trends of lung cancer burden in BRICS from 1990 to 2021 and its projection to 2035 - Wang, Yifan; Zhu, Jingwen; Wang, Shaoqiang; Zhou, Jihong (Frontiers in Oncology, 2025)
BackgroundLung cancer has become the malignant tumor with the highest morbidity and mortality in the world. This study aims to analyze the burden of lung cancer and risk factors associated with lung cancer in the BRICS from 1990-2021 and to project the burden of lung cancer in the BRICS from 2021-2035.MethodsThe Global Burden of Disease (GBD) 2021 database was searched to collect the incidence, prevalence, mortality, disability-adjusted life years (DALYs), and risk factors of lung cancer in the BRICS. Trends in lung cancer burden from 1990-2021 were analyzed using Joinpoint 4.9.1.0, and Bayesian age-period-cohort (BAPC) analyses were performed using R4.4.1 to project the disease burden of lung cancer from 2021-2035.ResultsAAPC(average annual percentage change) and EAPC(estimated average percentage change) of ASIR(age-standardized incidence), ASPR(age-standardized prevalence), ASMR(age-standardized mortality), and ASDR(age-standardized disability-adjusted life year) for lung cancer in Brazil, Russia, and Ethiopia 1990-2021 were less than 0. Egypt’s AAPC and EAPC for ASIR, ASPR, ASMR, and ASDR were all greater than 0 for 1990-2021, and China’s ASIR, ASPR, ASMR, and ASDR were all at the top of the BRICS in 2021. According to BAPC projection Brazil, Iran, Russia, and South Africa will have a decreasing trend in ASIR, ASPR, ASMR, and ASDR from 2021-2035. Egypt will have an increasing trend in ASIR, ASPR, ASMR, and ASDR from 2021-2035. With the exception of Ethiopia, the top tier level 1 and level 2 risk factors in the rest of the BRICS were behavioral factors and smoking factors, respectively.ConclusionThe BRICS still have a heavy burden of lung cancer, and there are significant differences in the burden of lung cancer among the BRICS. At the same time, many BRICS lung cancer prevention and control measures are worth learning from other developing countries.